The defensive design of printed-circuit boards. - Berrie, J. (IEEE spectrum)
This article on signal integrity has been approached from a slightly different angle than that normally pursued. There is an abundance of material on general signal integrity. Instead of repeating textbook techniques, however, the focus has been on two important issues: visualization, to assist intuition; and the basics of defensive design, which helps the designer get his or her design right the first time and allows some minor mistakes. The techniques described generally relate to digital boards using a fundamental frequency that is typically up to 2 GHz with signal transition times as low as 0.1 ns. Field solvers and ground planes are discussed as are connections and EMC aspects.